Exchange Transfusion with Dextran 40 in Polycythaemia Secondary to Hypoxic Lung Disease - Harrison, B. D. W. (1971)
In eight patients with polycythaemia secondary to hypoxic lung disease 10 elective exchange transfusions were performed to reduce red cell mass, packed cell volume (P.C.V.), and whole blood viscosity. The rationale for reducing P.C.V. is discussed. It is concluded that patients with P.C.V. of 60% or over will benefit from exchange transfusion and that most patients with P.C.V. over 50% and true polycythaemia will also benefit. We also confirm that the technique of exchange transfusion is a rapid, safe, and effective method of achieving large venesections and reducing red cell mass.